A comparative evaluation of nutritional characteristics, physical properties, and volatile profiles of sweet corn subjected to different drying methods. Issue 2 (16th December 2021) - Yao, Lianmou; Zhang, Yi; Qiao, Yongjin; Wang, Chunfang; Wang, Xiao; Chen, Bingjie; Kang, Ji; Cheng, Zhaohui; Jiang, Yongming
Abstract: Background and objectives: Fresh sweet corn is vulnerable to microbial damage and difficult to preservation at ambient temperature due to the high water and sugar contents. Therefore, in the present study, fresh sweet corn kernels were subjected to hot air drying (HAD), vacuum freeze drying (VFD), microwave drying (MD), and short‐ and medium‐wave infrared drying (SMIRD). Findings: Different drying ways of dehydrated sweet corns were compared in terms of physical properties, nutritional components, volatile compounds, and antioxidant capacity. After thermal treatment, sweet corn will form more volatile components and increase the flavor of sweet corn, while sweet corn treated by VFD will lose a lot of volatile components and weaken the flavor. Conclusions: The results demonstrated that VFD products exhibited higher rehydration capacity, more nutrient retention, and better antioxidant capacity with fewer volatile compounds. A total of 63 different volatile compounds were detected in dried sweet corns. The variety of volatile substances was the maximum in the SMIRD (55), followed by HAD (35), MD (28), fresh (22), and VFD (9). Significanceand novelty: Overall, this study would be fundamental for selecting more applicable drying methods to obtain desirable quality of dried sweet corn.